2004
DOI: 10.2175/193864704784138601
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Temperatures on BNR Process Performance

Abstract: The ever-expanding worldwide application of biological nutrient removal (BNR) technology is generating a greater appreciation for the performance of BNR processes under different operating conditions. This paper examines the effects of high process temperature on the biological phosphorus and nitrogen removal mechanisms and the sludge settling properties in BNR activated sludge processes. These effects are illustrated with data from three full-scale BNR facilities in which enhanced biological phosphorus remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The special sampling campaign was conducted during August/September 2013 when mixed liquor temperatures reached 30ºC. The commonly reported problem of losing biological P removal when temperatures exceed about 29ºC was not encountered (Rabinowitz et al, 2004;Lopez-Vazquez et al, 2008). …”
Section: Special Sampling and Concentration Profiling Resultsmentioning
confidence: 99%
“…The special sampling campaign was conducted during August/September 2013 when mixed liquor temperatures reached 30ºC. The commonly reported problem of losing biological P removal when temperatures exceed about 29ºC was not encountered (Rabinowitz et al, 2004;Lopez-Vazquez et al, 2008). …”
Section: Special Sampling and Concentration Profiling Resultsmentioning
confidence: 99%
“…The temperatures are typically above 80 o F (27 o C) in winter and have reached 107 o F (42 o C) during a summer heat wave. Despite the fact that this temperature is at the very end of acceptable temperatures for nitrification, as detailed in a review paper by Rabinowitz et al (2004), no detrimental impacts on the nitrification were observed.…”
Section: Temperature Concerns and Heat Balancementioning
confidence: 81%
“…It is not clear whether increased DO caused improved phosphorus uptake, but the authors speculate higher DO increased phosphorus uptake kinetics and thereby improved effluent quality. Rabinowitz et al, 2004 showed that temperature could have a major impact on phosphorus removal, and specifically that EBPR deteriorates at temperatures over 30 degC. Aeration basin mixed liquor temperatures in July reached 30 degC at the time of the upset, but also stayed up while the process recovered.…”
Section: July 2003 Operational Upsetmentioning
confidence: 99%